2010
DOI: 10.1039/b918964e
|View full text |Cite
|
Sign up to set email alerts
|

Cellular uptake and binding of guanidine-modified phthalocyanines to KRAS/HRASG-quadruplexes

Abstract: Guanidino-modified phthalocyanines are evaluated in vitro (polymerase-stop assays and FRET) and in cultured cells as G4-DNA ligands and modulators of gene transcription.The hypothesis that G-quadruplex DNA (or G4-DNA) is involved in transcription regulation is gaining support. 1 Recent studies have shown that, in addition to the telomeres, G4-DNA motifs are found with a high frequency in the regions surrounding transcription start sites of many genes. 2 G-quadruplex structures have been identified in protoonco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
53
0
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 72 publications
(57 citation statements)
references
References 31 publications
(11 reference statements)
1
53
0
3
Order By: Relevance
“…9b shows that 10 M DIGP and Zn-DIGP weakly compete with the binding of MAZ to the GA-duplex. In a recent study we found that DIGP and Zn-DIGP interact with the murine KRAS quadruplex with a K D between 10 Ϫ7 and 10 Ϫ6 M (21). Polymerase stop assays showed that these ligands efficiently stabilize the G-quadruplex formed by the GA-element (21).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…9b shows that 10 M DIGP and Zn-DIGP weakly compete with the binding of MAZ to the GA-duplex. In a recent study we found that DIGP and Zn-DIGP interact with the murine KRAS quadruplex with a K D between 10 Ϫ7 and 10 Ϫ6 M (21). Polymerase stop assays showed that these ligands efficiently stabilize the G-quadruplex formed by the GA-element (21).…”
mentioning
confidence: 99%
“…In a recent study we found that DIGP and Zn-DIGP interact with the murine KRAS quadruplex with a K D between 10 Ϫ7 and 10 Ϫ6 M (21). Polymerase stop assays showed that these ligands efficiently stabilize the G-quadruplex formed by the GA-element (21). Indeed, circular dichroism spectra obtained at various temperatures (20 -90°C) showed that the T M of the G-quadruplex in the presence of DIGP (r ϭ 4) increased from 68 to Ͼ90°C in 50 mM KCl (supplemental Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Bulky porphyrin derivatives H 2 -TMPipEOPP, H 2 -TMPy2PP, H 2 -GP, H 2 -DIGPor and H 2 -TPyEtCAP can perfectly discriminate between quadruplex and double-stranded DNA [63,69,71,[116][117][118][119][120]. Their binding constants for quadruplex DNA is comparable to that of best G4 ligands [120].…”
Section: Interaction Of Porphyrins With G-quadruplex Dnamentioning
confidence: 63%
“…These derivatives are cationic phtalocyanines/porphyrazines [111,118,[126][127][128][129] or core-expanded porphyrins [130,131]. It is striking to note that negatively charged compounds such as Nmethylmesoporphyrin IX (NMM) [44,45,132,133], protoporphyrin IX [134], hemin (Fe IIIprotoporphyrin IX) [135][136][137] with two carboxylic groups or tetraphtalocyanines with four sulfonate groups [138][139][140] are endowed with G-quadruplex binding capability.…”
Section: Interaction Of Porphyrins With G-quadruplex Dnamentioning
confidence: 97%